Carbon sequestration of man-made forests: sequestration estimate and its bearings on CDM - Morikawa, Y.; Ohta, S.; Hiratsuka, M.; Toma, T. (Forestry Research Institute, 2002)
This study estimates that sequestrated carbon by industrial tree plantations is at about 10 tC/ha/yr in good sites. The carbon accumulated by rehabilitation forests is not always less than that of industrial plantations. Selecting the suitable pecies could be one of the essential factors to succed and preserving forests. Rehabilitation forests in Lombok and Benakat in South Sumatra sites are regarded as the successful cases. While annual carbon accumulation by naturally regenerated vegetation at baselines in Lombok site amounts to 2.9-3.2 tC/ha/yr, the net carbon accumulation of this site ranges from 2.9 to 5.7 tC/ha/yr. Establishing forests has markedly increased the carbon accumulation in this area. The carbon accumulation at baseline at Benakat site is 1.6-2.8 tC/ha/yr. It is almost the same as that of Lombok site. The above ground carbon dry weight of 20-year-old S. macrophylla planted for rehabilitation purposes is 6.6 tC/ha/yr. These results suggest that, in short rotation, the carbon accumulation of rehabilitation forests is not markedly different from that of industrial plantations. Conserving the rehabilitation forests for a long time would therefore, be one of the most rational practices for storing carbon on degraded lands sustainably.